Understanding Resident Intention and Behavior toward Water Conservation Initiative in the Upstream of West Java, Indonesia - Prasetyo Nugroho; Apriliyanti Dwi Rahayu; Rany Juliani; Indarto; Alfian Dwi Cahyo; Nida Ankhoviyya; Edwin Gumilar; Denni Susanto; Adi Nugroho (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Upstream areas have long been targeted as the priority of water conservation initiatives. While earlier studies often considered underlying socio-psychological factors determining residents' intention and behaviors in water conservation, studies that focused on the resident's intention and behavior in upstream areas, where water is abundant, remain underexplored. The current study used socio-psychological constructs of the theory of planned behavior (TPB), i.e., subjective norm, attitudes toward behavior, and perceived behavioral control, to analyze the determinants of water conservation intention and behavior in two villages upstream of West Java (i.e., Cibeusi and Sanca villages), Indonesia. A total of 200 usable questionnaires were retrieved. Structural equation modeling was used to determine the linkages and strength of relationships among constructs. There was evidence that residents perceived behavioral control exerted the most significant influence on residents' water conservation intention and behavior. Moreover, perceived behavioral control was an effective mediator of the linkage between attitude and residents' intention and behavior. The findings confirmed the suitability of TPB in explaining interrelationships among determinant factors that explain residents' intention and behavior, albeit with different mechanisms and effects. The study implied that increasing awareness of the value of water conservation would significantly affect residents' attitudes, which subsequently increased their willingness to perform water conservation efforts. Keywords: attitude, Cipunagara watershed, theory of planned behavior, Subang